ANALISIS KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KEPRIBADIAN EXTROVERT DAN INTROVERT - Aprillia, Dwi; Mattoliang, Lisnasari Andi; Yuliany, Nur; Abrar, Andi Ika Prasasti; Ismail, Wahyuni (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This research is driven by the importance of mathematical reasoning skills as a foundation for understanding concepts and solving mathematical problems, alongside indications of low proficiency in these skills, which is suspected to be linked to differences in personality types. The primary objective of this study is to determine the differences in mathematical reasoning abilities between extroverted and introverted students and to analyze the reasoning characteristics of each personality type. This study employs a mixed-methods approach with a sequential explanatory design, beginning with quantitative data collection through reasoning tests and the Eysenck Personality Inventory questionnaire administered to 65 grade XII MIA students at MAN 1 Bulukumba, followed by in-depth interviews with six selected subjects. The results show that: 1) there is a significant difference in mathematical reasoning abilities between extroverted and introverted students, with a significance value of 0.009; 2) Extroverted students tend to think quickly and rush, often skipping important steps in problem-solving. Conversely, introverted students tend to be more thorough and systematic in organizing their solution steps, although in some cases they still fall short in double-checking or drawing conclusions. The implication of this research is the importance of learning strategies tailored to personality types to optimize students' mathematical reasoning abilities.